The National Planning Policy Framework and Archaeology - Taryn Nixon (Papers from the Institute of Archaeology, 2013)
This helpful addition to the literature and thinking around planning and archaeology comes at an exciting time, as the Localism Act, streamlining of non-planning consents, economic recession and political change all converge. It is striking, in the review of archaeology and planning policy over some thirty years, what a revolution we have experienced in that time. When PPGs 16 and 15 were introduced in 1990s, they professed not to place any new responsibilities on local authorities, but in practice their implementation required a new zealousness, a significant new commitment and in many cases new skillsets among local authorities. Despite the challenges for even-handed implementation, it is to the enormous credit of authorities around the country that the PPG policies were implemented to the extent they were.
Keywords: National Planning Policy Framework; planning; development